Trapa natans L. Extract Attenuates Inflammation and Oxidative Damage in Cisplatin-Induced Cardiotoxicity in Rats by Promoting M2 Macrophage Polarization - Vesna Matovic; Biljana Ljujic; Ivana Radojevic; Gorica Đelic; Marina Miletic Kovacevic; Suzana Zivanovic; Milos Papic; Nevena Milivojevic; Ivica Petrovic; Marina Gazdic Jankovic (Mediators of Inflammation)
Conclusion: Our study provides the evidence that TNE ameliorates cisplatin-induced cardiotoxicity in rats by reducing inflammation and oxidative stress via promoting M2 macrophage polarization.